2018
DOI: 10.1007/s12519-018-0192-0
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric clinical practice guidelines in China: still a long way to go

Abstract: Clinical practice guidelines provide optimal patient care recommendations, which are important tools for promoting the equality of health care services and saving healthcare resources in China [1]. The evidence-based clinical guidelines are specific to clinical problems and are developed through systematic reviewing to help clinicians and patients make appropriate decisions. Chen et al. revealed several limitations in adoption and adaptation of Chinese Guidelines including (1) rarely using systematic review to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Therefore, there is an urgent requirement for necessary pediatric clinical practice and nursing guidelines to improve the pediatric healthcare and pediatric nursing system in China. 44 In the present study, the assessment of nursing care in children infected with rotavirus implied that quality health care is important for all people, especially pediatric children with severe diarrhea. This is because pediatric children with severe diarrhea require special care for hydration to meet growth and developmental need.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, there is an urgent requirement for necessary pediatric clinical practice and nursing guidelines to improve the pediatric healthcare and pediatric nursing system in China. 44 In the present study, the assessment of nursing care in children infected with rotavirus implied that quality health care is important for all people, especially pediatric children with severe diarrhea. This is because pediatric children with severe diarrhea require special care for hydration to meet growth and developmental need.…”
Section: Discussionmentioning
confidence: 82%
“…The paediatric guidelines are particularly important for paediatric healthcare and for improvements in medical equality throughout China. 79 This guideline not only develops recommendations, but also faithfully reflects the current evidence regarding intravenous AZM use in children, which will help to improve clinical practice and encourage more well-designed and high-quality studies in the future.…”
Section: Statementmentioning
confidence: 99%
“…However, the previous studies assessing some CPGs in China have indicated that improvements in the quality, transparency, and usability of the guidelines are required which included identifying, appraising, and synthesizing the evidence underpinning the guideline recommendations, and paying more attention in dealing with and reporting conflicts of interest (3)(4)(5)(7)(8)(9)(10)(11)(12). The whole situation of CPGs development is unclear, especially in the recent decade including the extent to which CPGs in China currently utilize rigorous methods.…”
Section: Introductionmentioning
confidence: 99%